2010
DOI: 10.1016/j.lfs.2009.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Bi- or multifunctional opioid peptide drugs

Abstract: Strategies for the design of bi-or multifunctional drugs are reviewed. A distinction is made between bifunctional drugs interacting in a monovalent fashion with two targets and ligands containing two distinct pharmacophores binding in a bivalent mode to the two binding sites in a receptor heterodimer. Arguments are presented to indicate that some of the so-called "bivalent" ligands reported in the literature are unlikely to simultaneously interact with two binding sites. Aspects related to the development of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
215
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(223 citation statements)
references
References 59 publications
8
215
0
Order By: Relevance
“…Therefore, the antiserum primarily recognizes DOR1, although an excessive amount of antiserum might generate nonspecific binding. Using the antibodies above at a dilution of 1:30,000, we found that DORs were present in peptidergic and vanilloid receptor type 1-ir small neurons ( Interestingly, we found the presence of DORs on the cell surface in ∼14% of DRG neurons when we tested another antibody, now against DOR1 [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] (1:60,000-120,000; Alomone) that also recognized Myc-DOR1 expressed in HEK293 cells ( Fig. 3 H and I and Fig.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Therefore, the antiserum primarily recognizes DOR1, although an excessive amount of antiserum might generate nonspecific binding. Using the antibodies above at a dilution of 1:30,000, we found that DORs were present in peptidergic and vanilloid receptor type 1-ir small neurons ( Interestingly, we found the presence of DORs on the cell surface in ∼14% of DRG neurons when we tested another antibody, now against DOR1 [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] (1:60,000-120,000; Alomone) that also recognized Myc-DOR1 expressed in HEK293 cells ( Fig. 3 H and I and Fig.…”
Section: Resultsmentioning
confidence: 90%
“…These patterns are shown by immunostaining of both exogenously expressed Myc-DOR1 and endogenous DORs using antibodies against DOR1 3-17 or DOR1 [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . Thus, these antibodies against different N-terminal regions of DOR1 might recognize DORs in different states of activation, conformation, glycosylation, and/or palmitoylation (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations